Every Living Thing - Cynthia Rylant (New York, United States SIMON & SCHUSTER, 2009)
Here are twelve deeply moving short stories from the perceptive pen of Cynthia Rylant. Each captures the moment when someone's life changes -- when an animal causes a human being to see things in a different way, and, perhaps, changes his life.
Keywords: Realistic Fiction -- Realistic Fiction